Summary of Reported Whale-Vessel Collisions in Alaskan Waters. (17th July 2012) - Neilson, Janet L.; Gabriele, Christine M.; Jensen, Aleria S.; Jackson, Kaili; Straley, Janice M.
Abstract : Here we summarize 108 reported whale-vessel collisions in Alaska from 1978–2011, of which 25 are known to have resulted in the whale's death. We found 89 definite and 19 possible/probable strikes based on standard criteria we created for this study. Most strikes involved humpback whales (86%) with six other species documented. Small vessel strikes were most common (<15 m, 60%), but medium (15–79 m, 27%) and large (≥80 m, 13%) vessels also struck whales. Among the 25 mortalities, vessel length was known in seven cases (190–294 m) and vessel speed was known in three cases (12–19 kn). In 36 cases, human injury or property damage resulted from the collision, and at least 15 people were thrown into the water. In 15 cases humpback whales struck anchored or drifting vessels, suggesting the whales did not detect the vessels. Documenting collisions in Alaska will remain challenging due to remoteness and resource limitations. For a better understanding of the factors contributing to lethal collisions, we recommend (1) systematic documentation of collisions, including vessel size and speed; (2) greater efforts to necropsy stranded whales; (3) using experienced teams focused on determining cause of death; (4) using standard criteria for validating collision reports, such as those presented in this paper.